y=3(-11/2)-2

Simple and best practice solution for y=3(-11/2)-2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for y=3(-11/2)-2 equation:



y=3(-11/2)-2
We move all terms to the left:
y-(3(-11/2)-2)=0
We multiply all the terms by the denominator
y*2)-2)-(3(-11=0
Wy multiply elements
2y^2-11=0
a = 2; b = 0; c = -11;
Δ = b2-4ac
Δ = 02-4·2·(-11)
Δ = 88
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$y_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$y_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

The end solution:
$\sqrt{\Delta}=\sqrt{88}=\sqrt{4*22}=\sqrt{4}*\sqrt{22}=2\sqrt{22}$
$y_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(0)-2\sqrt{22}}{2*2}=\frac{0-2\sqrt{22}}{4} =-\frac{2\sqrt{22}}{4} =-\frac{\sqrt{22}}{2} $
$y_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(0)+2\sqrt{22}}{2*2}=\frac{0+2\sqrt{22}}{4} =\frac{2\sqrt{22}}{4} =\frac{\sqrt{22}}{2} $

See similar equations:

| 6x-1+11x+4+75=180 | | 76-2x=88-3x | | -2x+10+5x=-5 | | 2m+15=-3 | | 2(2a-1)=7a+14.6 | | 3x-8=4+4(x+5) | | 4x-5=-x+5 | | (9x-4)=(3x=6) | | 14x(10)-7=21 | | 4/3x+3/5=6/15 | | -8=-1/13a | | 13-3b-2b=11 | | 2(5g-1=3 | | (x*x*x)=27/729 | | 5x/6=-30 | | 3x/4=-60 | | 16(x-3)=32 | | 19x.36=6.87 | | 1n-5=2 | | 1n+5=2 | | z-4.8=6.1 | | n/14=-14 | | -9x+7x=-24+24 | | -53.6=-6.7c | | (x+2)*(x-3)-(x+1)^2=0 | | 2(4y-4)-3=21 | | Y+4x=11.X=-1,0,4 | | x+2x+x+5=57 | | 11u+99=-77 | | 5.2=d/8 | | 23.4=-3.9s | | 2(x-5=20x) |

Equations solver categories